Marketing Non-Degree Supplementary Programs in Tertiary Education Organizations in Russia - Trostina, Kira (European Scientific Journal, ESJ, 2017)
Successful entrepreneurial activity of a university determines its local and international competitiveness and budgeting efficiency. Modern global educational practices are witnessing a growing tendency to fund-raising from non-core activities via expanding the scope of extra-curricular fee-paying programs and educational events. Price-sensitive factors, which form and manage the demand for differentiated curricula in supplementary education in an economic university, are analyzed. A structured approach to increasing the consumer value of for-profit non-degree programs is suggested. Additional revenue generation is used to improve the service and contributes to the autonomy of a tertiary education organization.